The impact of exercise-only-based rehabilitation on depression and anxiety in patients after myocardial infarction. (1st June 2017) - Korzeniowska-Kubacka, Iwona; Bilińska, Maria; Piotrowska, Dorota; Stepnowska, Monika; Piotrowicz, Ryszard
Abstract: Aim: The aim of the study was to assess the effectiveness of exercise training on depression, anxiety, physical capacity and sympatho-vagal balance in patients after myocardial infarction and compare differences between men and women. Methods: Thirty-two men aged 56.3±7.6 years and 30 women aged 59.2±8.1 years following myocardial infarction underwent an 8-week training programme consisting of 24 interval trainings on cycloergometer, three times a week. Before and after completing the training programme, patients underwent: depression intensity assessment with the Beck depression inventory; anxiety assessment with the state–trait anxiety inventory; a symptom-limited exercise test during which were analysed: maximal workload, duration, double product. Results: In women the initial depression intensity was higher than in men, and decreased significantly after the training programme (14.8±8.7 vs. 10.5±8.8; P <0.01). The anxiety manifestation for state anxiety in women was higher than in men and decreased significantly after the training programme (45.7±9.7 vs. 40.8±0.3; P <0.01). Of note, no depression and anxiety manifestation was found in men. Physical capacity improved significantly after the training programme in all groups, and separately in men and in women. Moreover, an 8-week training programme favourably modified the parasympathetic tone. Conclusions: Participating in the exercise training programme contributed beneficially to a decrease in depression and anxiety manifestations in women post-myocardial infarction. Neither depression nor anxiety changed significantly in men. The impact of exercise training on physical capacity and autonomic balance was beneficial and comparable between men and women.